2011
DOI: 10.1242/jcs.078055
|View full text |Cite
|
Sign up to set email alerts
|

RNF41 (Nrdp1) controls type 1 cytokine receptor degradation and ectodomain shedding

Abstract: Cytokines, such as interferons, erythropoietin, leptin and most interleukins, signal through type 1 cytokine receptors and activate the canonical JAK–STAT pathway. Aberrant cytokine signalling underlies numerous pathologies and adequate, temporary receptor activation is therefore under tight control. Negative-feedback mechanisms are very well studied, but cellular sensitivity also depends on the number of receptors exposed at the cell surface. This is determined by the equilibrium between receptor synthesis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 48 publications
1
73
1
2
Order By: Relevance
“…Far less attention has been paid to a possible role for metalloproteases in the generation of sgp130, probably because this is generally believed to solely result from alternative mRNA splicing (2). However, recent studies showed that metalloproteases participate in the generation of soluble forms of the leukemia inhibitory factor receptor (LIFR) (22) and of the IL-27R WSX-1 (23), two other ␤ receptors that are used by IL-6 family of cytokines (24).…”
Section: Gp130 Can Be Shed By Adam10 and Adam17 Albeit Withmentioning
confidence: 99%
“…Far less attention has been paid to a possible role for metalloproteases in the generation of sgp130, probably because this is generally believed to solely result from alternative mRNA splicing (2). However, recent studies showed that metalloproteases participate in the generation of soluble forms of the leukemia inhibitory factor receptor (LIFR) (22) and of the IL-27R WSX-1 (23), two other ␤ receptors that are used by IL-6 family of cytokines (24).…”
Section: Gp130 Can Be Shed By Adam10 and Adam17 Albeit Withmentioning
confidence: 99%
“…The interactome of a designated protein of interest can be determined efficiently, as such enabling "pathway walking" where serial identification of novel binding proteins supports signal transduction pathway mapping. The identification of RNF41 interaction partners is an example of such an approach: RNF41 itself was found an interaction partner of the leptin receptor complex in a MAPPIT screen (20), we here report the identification VPS52 and ASB6 as RNF41 binding proteins, and the analysis of additional MAPPIT screens to identify downstream interactors is currently ongoing (Masschaele et al, in preparation; De Ceuninck et al, in preparation). Apart from mapping the basic interactome of a protein, we showed that also dynamic aspects of the interaction pattern of a particular bait can be captured at this scale.…”
Section: Discussionmentioning
confidence: 77%
“…Also the control prey plasmid expressing unfused gp130 (13), the plasmid encoding the C-terminal HMGCR prey (19), the STAT3-dependent firefly luciferase reporter pXP2d2-rPAPI-luciferase (4), pMet7-RNF41-Etag (20), pMet7-Flag-RNF41 (21), pMet7-Flag-SV40 large T (20), pCLG-DHFR (15), pCLG-GR (22), and the p(GRE)250hu.IL6P-lucϩ GRE-luciferase reporter plasmid (22) were as described before. The pXP2d2-rPAPImKate2 reporter gene plasmid was generated by replacing the firefly luciferase sequence in pXP2d2-rPAPI-luciferase (4) with the mKate2 encoding sequence (23).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations